2021
DOI: 10.1111/jch.14156
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of adolescent hypertension by ambulatory blood pressure monitoring using adult norms and association with left ventricular hypertrophy

Abstract: The prevalence of hypertension (HTN) in children and adolescents has been on the rise in the last decade. 1 This increased prevalence of HTN has highlighted the need for further research and guidelines for diagnosis and management. Blood pressure norms in pediatrics are derived from population data for both clinic and ambulatory blood pressures as opposed to adult norms which are based on outcome data. Because the pediatric definition is based on age, sex, and height derived from population data, norms for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…One retrospective single-center study showed better prediction of LVH with the higher ESH cut points versus the ACC/AHA values. 15 In all studies, DBP was not significantly associated with LVH 13–16 or predicted progression to end-stage kidney disease. 14…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…One retrospective single-center study showed better prediction of LVH with the higher ESH cut points versus the ACC/AHA values. 15 In all studies, DBP was not significantly associated with LVH 13–16 or predicted progression to end-stage kidney disease. 14…”
mentioning
confidence: 76%
“…It has also led investigators to explore the impact of using the new adult criteria for diagnosing ambulatory hypertension in children and adolescents. [13][14][15][16] In alignment with the updated BP classification schema recommended in the 2017 AAP CPG, these studies specifically examined the use of adult ABPM thresholds in adolescents ≥13 years of age. Not surprisingly, in all studies, the prevalence of ambulatory hypertension was significantly higher when using the lower ACC/AHA static adult cut points than when using the higher pediatric percentile-based thresholds.…”
mentioning
confidence: 99%
“…To avoid this apparent paradox, due to the higher peripheral amplification of pressure wave in this range of age 28,29 , as well as to the greater physical activity especially during day-time 26 , application of adult ABPM norms has been suggested for pediatric age 27,30 .…”
Section: Ambulatory Blood Pressure Monitoring (Abpm)mentioning
confidence: 99%
“…As for office BP, the 95th 24-h mean systolic and diastolic BP percentiles are used as HTN thresholds in children and younger adolescents. However, whether to use percentiles or fixed cut-off BP values to diagnose HTN in adolescents is a matter of debate ( 30 , 31 ). Currently, the 95th percentile is used as a HTN threshold as long as the values are inferior to the accepted criteria for adults ( 10 ).…”
Section: Out Of Office Blood Pressurementioning
confidence: 99%